CFD Modelling of Finned-tube CO2 Gas Cooler for Refrigeration Systems. (March 2019) - Zhang, Xinyu; Ge, Yunting; Sun, Jining; Li, Liang; Tassou, Savvas A.
Abstract: As a main component in a refrigeration system, finned-tube CO2 gas cooler plays an important role to the system performance and thus needs to be thoroughly investigated. To achieve this, some effective parameters including the CO2 and air fluid velocity fields, temperature profiles and heat transfer characteristics at different operating conditions are predicted and analysed by means of Computational Fluid Dynamics (CFD) modelling and simulation. It is noted that CFD modelling can accurately obtain the local heat transfer coefficients of both air and refrigerant sides, which are difficult to be predicted by conventional empirical correlations. This paper investigates the effect of varied operational parameters on local heat transfer coefficients and temperature profiles of the working fluids in a finned-tube CO2 gas cooler by means of CFD modelling. As one of the simulation results, it is found that the approach temperature decreases with increased air inlet velocity. The model has been compared and validated with experimental measurements and literature correlations. The research methods and outcomes can be used for further investigation and optimization in this area.